Esofagitis por reflujo en el adulto: Round table XXVII Uruguayan Congress of Surgery: coordinator Oscar Balboa - Balboa, Oscar; Cardozo, Tabaré; Chifflet, Juan; Estapé, Gonzalo; Romano, Dante; Sojo, Enrique; Soto, José A (Cirugía del Uruguay, 1977)
The primordial element in this pathology e-s the appearance of gas reflux, troesophageal conditioned by a failure of the mechanisms cardial continence, within which are places special emphasis on the • esophageal sphincter lower (E.E.I.) indicating the value of studies manometric and pH of this region and its radiological correlation.